Feasibility and Acceptability of Using Television Clips to Teach Communication Skills. Issue 3 (20th September 2022) - Hoffman, Beth L.; Sidani, Jaime E.; Wolynn, Riley; Morgan, Allison; Calhoun, Bridget C.
Abstract : Introduction: The purpose of this study was to conduct an innovative seminar that was developed by using clips from the television program ER to teach/reinforce key concepts of effective communication for didactic phase physician assistant (PA) students. Methods: Interactive, 2-hour, small group seminars were conducted as part of the PA curriculum. Demographic data, as well as information about prior exposure to medical-related television shows and interest in specific medical disciplines, were collected at baseline. The evaluation of this unconventional teaching strategy was completed via a post-activity self-administered, electronic survey. Descriptive statistics were calculated for closed-ended questions, and a thematic analysis approach was used to examine open-ended questions. Results: Approximately two-thirds (n = 49) of the students who attended the seminars completed both the baseline and post-activity surveys. The seminars were well-received, with 94% of respondents indicating they would like to participate in similar trainings in the future. The primary suggestion was to use clips from multiple television programs. Discussion: The results suggest that this instructional format was highly acceptable to modern PA students, who yearn for an amalgamation of education and entertainment. Future work could examine the influence of the seminar on students' communication in clinical environments.